2021
DOI: 10.1002/chem.202100315
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of New Withaferin A Inspired Hedgehog Pathway Inhibitors

Abstract: Withanolides constitute a well‐known family of plant‐based alkaloids characterised by widespread biological properties, including the ability of interfering with Hedgehog (Hh) signalling pathway. Following our interest in natural products and in anticancer compounds, we report here the synthesis of a new class of Hh signalling pathway inhibitors, inspired by withaferin A, the first isolated member of withanolides. The decoration of our scaffolds was rationally supported by in silico studies, while functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Besides, in their central moieties, withaferin B contains octadecan-5-yl, whereas withaferin A contains octadec-4-en-3-one. Of note, withaferin A has been reported to be a potential anti-cancer molecule that can inhibit cell proliferation, cell migration, and cell invasion [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Similarly, withaferin B, bound to the FAM72A-UNG2 heterodimer, could possibly block FAM72A-UNG2 signaling pathways in cancer cells [ 26 , 29 ]; however, thus far, the biological and therapeutic properties of withaferin B remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in their central moieties, withaferin B contains octadecan-5-yl, whereas withaferin A contains octadec-4-en-3-one. Of note, withaferin A has been reported to be a potential anti-cancer molecule that can inhibit cell proliferation, cell migration, and cell invasion [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Similarly, withaferin B, bound to the FAM72A-UNG2 heterodimer, could possibly block FAM72A-UNG2 signaling pathways in cancer cells [ 26 , 29 ]; however, thus far, the biological and therapeutic properties of withaferin B remain unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The withanolides are naturally found steroidal lactones that impart a distinctive earthy odor and flavor to Ashwagandha (Sangwan et al, 2017). Withaferin A was the primary isolated member of this group in 1965 (Bonandi et al, 2021).…”
Section: Morphological Characteristics Distribution Chemical Composit...mentioning
confidence: 99%
“…In 2021, the Passarella group proposed simplifying the structure to contain cyclic carbamates with the ultimate goal of synthesizing and evaluating compound 1 ( Figure 4 D) [ 103 ]. However, stereoisomers of this compound ultimately proved inactive against Hh signaling.…”
Section: Chemotherapies That Target Hedgehog Signalingmentioning
confidence: 99%
“…Two pathway intermediates, 13b ( Figure 4 E) and 14b ( Figure 4 F), successfully inhibited SMO with racemic IC 50 values of 7.4 µM and 13.0 µM, respectively. Enantioselective synthesis revealed that (+)-13b and (−)-14b were the more potent inhibitors with IC 50 values around 6 µM compared to their enantiomers at 11–16 µM [ 103 ]. While it is surprising that deprotection of 14b to yield compound 1 eliminates activity, the tert-butyl(chloro)diphenylsilane (TBDPS) protecting group is highly lipophilic and might significantly impact protein interaction.…”
Section: Chemotherapies That Target Hedgehog Signalingmentioning
confidence: 99%